Parental knowledge, attitude, and practice regarding the importance of primary dentition of their children in Kerala, India - Vennila Chandran; R Balagopal Varma; Teena Mary Joy; Venkitachalam Ramanarayanan; Bhat Sangeetha Govinda; Medhini Madhava Menon (Wolters Kluwer Medknow Publications, 2019)
Background: The primary dentition for children is, perhaps, the most essential and yet the most neglected concern by a parent. Often, these parents who are responsible for the health of the primary dentition of their children feel that primary teeth eventually shed, and hence does not deserve heed on providing adequate oral health. Aim: The aim of this study was to evaluate the parental knowledge, attitude, and practices on the importance of primary dentition of their children. Materials and Methods: An institution-based cross-sectional study was done among parents of children below 12 years of age. A 25-item semi-structured questionnaire, in both English and Malayalam languages, was prepared for the data collection. Statistical analysis was done using the Statistical Package for the Social Sciences. The quantitative variables were described as mean and standard deviation. To find out the association between categorical variables, the Chi-square test was applied. A multivariate logistic regression was done to find the independent predictors of knowledge. P <0.05 was considered statistically significant. Results: A total of 473 parents participated in the study. About 55.4% of the parents were found to have poor knowledge, while 58.4% and 55.2% of the parents were found to have good attitude and practice about the importance of primary dentition, respectively. There was a significant relationship between knowledge ( P = 0.0001), attitude ( P = 0.001), and practices ( P = 0.017) of the parents with their level of education. Furthermore, a significant association was found between the knowledge of parent and the area of residence ( P = 0.036) and attitude of the parent with that of the gender of the child ( P = 0.043). Conclusions: Majority agreed that primary teeth were important along with the knowledge that dental diseases were related to health problems. Education played a major role in parental awareness of primary dentition.